PENGARUH DANA PIHAK KETIGA, INFLASI, DAN TINGKAT SUKU BUNGA KREDIT TERHADAP PERMINTAAN KREDIT INVESTASI BANK PEMERINTAH DAERAH DI INDONESIA - Gusnimar Gusnimar; Sri Ulfa Sentosa (Universitas Negeri Padang, 2019)
This study aims to find out how the influence of deposits, inflation, and credit interest rates on the demand for investment loans from Government Banks in Indonesia. The data used are secondary data in the form of time series from 2010: Q1 to 20108: Q4, with the technique of collecting documentation data and library studies obtained from relevant institutions and agencies. The variables used are Investment Credit Demand (Y),deposits (X1), inflation (X2), and credit interest rates (X3). The research method used is Ordinary last Square (OLS). The results of the study show that (1) deposits and inflation have a positive and significant effect on the demand for investment credit, (2) the credit interest rate has a negative and significant effect on the demand for investment credit, and (3) deposits, inflation, and rates Credit interest has a significant effect on the demand for investment credit at Regional Government Banks in Indonesia